Even more parts : idioms from head to toe - Arnold, Tedd. (New York : Dial Books for Young Readers, 2004)
A young boy is worried about what will happen to his body when he hears such expressions as "I'm tongue-tied, " "don't give me any of your lip, " and "I put my foot in my mouth." Tedd Arnold's previous books about Chip, Parts and More Parts, are raucous, creative knee-slappers that have become true kid favorites--perhaps because they so humorously express the worries all kids have as they get to know their bodies: worries about belly button fuzz and earwax and loose teeth. Now here's the funniest Parts book yet--one that reintroduces our ner-vous hero while also depicting more than 100 body-part idioms. I lost my head, my nose is running, I sang my heart out . . . You won't be able to keep a straight face as you enjoy this clever, wacky, boldly illustrated book.
A Junior Library Guild selection.
Keywords: Human body -- Fiction; Figures of speech -- Fiction; Stories in rhyme; Human body -- Juvenile fiction; Figures of speech -- Juvenile fiction